Optimal linear commodity taxation under optimal non-linear income taxation - Jacobs, Bas; Boadway, Robin (Journal of public economics, 2014)
This paper analyzes optimal linear commodity taxes joint with non-linear income taxes. We provide optimal tax rules based on empirically observable elasticities, earnings and commodity demands. We demonstrate that commodities should be taxed/subsidized if – conditional on earnings – doing so boosts labor supply as the critical role of commodity taxation is to alleviate distortions on labor supply caused by income taxation. We extend the standard formula for optimal non-linear income taxation for the presence of optimal linear commodity taxes. We correct parts of the literature by showing that the optimal second-best allocations derived by Atkinson and Stiglitz (1976, 1980) cannot be supported by linear commodity taxes. •This paper derives optimal linear commodity taxes under non-linear income taxation.•A modified ABC-formula for optimal non-linear income taxation is presented.•Commodity taxes are only used to alleviate distortions on labor supply.•Commodity taxes are lower if commodities are stronger complements to labor supply.•Atkinson and Stiglitz' (1976, 1980) results do not apply to linear commodity taxes.